2021
DOI: 10.3389/fenvs.2021.624070
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbiome Structure and Function in Ecopiles Used to Remediate Petroleum-Contaminated Soil

Abstract: The soil microbiome consists of a vast variety of microorganisms which contribute to essential ecosystem services including nutrient recycling, protecting soil structure, and pathogen suppression. Recalcitrant organic compounds present in soils contaminated with fuel oil can lead to a decrease in functional redundancy within soil microbiomes. Ecopiling is a passive bioremediation technique involving biostimulation of indigenous hydrocarbon degraders, bioaugmentation through inoculation with known petroleum-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 99 publications
1
13
0
1
Order By: Relevance
“…Lh also has a rhizosphere colonized by hydrocarbonoclastic bacteria and fungi (González-Moscoso et al 2019). The adaptation of these microorganisms to the presence of crude oil suggests the presence of genes related to hydrocarbon degradation similar to those found in the bacteria Pusillimonas, Dietzia, Bradyrhizobium, Azospirillum, and Azotobacter (Arias-Trinidad et al 2017; Wang et al 2021). When associated with the roots of Lh, these bacteria stimulate the removal of TPH from the soil (Orocio-Carrillo et al 2019).…”
Section: Zuzolo Et Al 2021)mentioning
confidence: 62%
“…Lh also has a rhizosphere colonized by hydrocarbonoclastic bacteria and fungi (González-Moscoso et al 2019). The adaptation of these microorganisms to the presence of crude oil suggests the presence of genes related to hydrocarbon degradation similar to those found in the bacteria Pusillimonas, Dietzia, Bradyrhizobium, Azospirillum, and Azotobacter (Arias-Trinidad et al 2017; Wang et al 2021). When associated with the roots of Lh, these bacteria stimulate the removal of TPH from the soil (Orocio-Carrillo et al 2019).…”
Section: Zuzolo Et Al 2021)mentioning
confidence: 62%
“…compared to other AK6 members, this assumption might appear contradictory to the general belief assigning most abundant community members as the most influential in pollutant degradation process. However, this does not have to be always the case and some studies reported a crucial role of the so-called “rare biosphere” or “conditionally rare taxa” in pollutants biodegradation ( Wang et al, 2017 , 2021 ; Xu et al, 2018 ; Pascoal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogenophaga, Hyphomicrobium and Dokdonella have been linked before to the treatment of alkanes and also of complex hydrocarbons (Pascual et al, 2020;Rojas-Gätjens et al, 2020). Moreover, it has been recently discovered that members of the family Phyllobacteriaceae have the necessary genes for the metabolism of complex alkanes (Wang et al, 2021).…”
Section: Bacterial Diversity and Community Structurementioning
confidence: 99%